THE INFLUENCE OF COMPETENCY, COMPENSATION AND JOB SATISFACTION ON VILLAGE HEAD PERFORMANCE IN VILLAGE FINANSIAL MANAGEMENT OF KERINCI REGENCY - Putra, Ade Nurma Jaya (RC-INSTITUT, 2018)
The aim of the study was to uncover the influence of competency, compensation, and job satisfaction on village head performance in village financial management of Kerinci Regency, either directly or indirectly. This study was approached by using quantitative method. The exogenous variables were competency (X1), compensation (X2), job satisfaction as intervening variable (X3), and village head performance (Y) as the endogenous variable. The population of the study is 285 village heads in Kerinci Regency. The 48 samples were taken in two phases; cluster sampling and random sampling technique. The data were collected by using a valid and a reliable questionnaire and were analyzed by using path analysis. The study found: (1) There was direct influence of competency on job satisfaction for 22.74% with 0.00 significance level; (2) There was direct influence of compensation on job satisfaction for 26.93% with 0.00 significance level; (3) There was direct influence of competency on village head performance for 25% with 0.00 significance level; (4) There was direct influence of compensation on village head performance for 2.72% with 0.0027 significance level; (5) There was direct influence of job satisfaction on village head performance for 11.90% with 0.00 significance level; (6) There was indirect influence of competency on village head performance interfered by job satisfaction for 8.14% which Tvalue was bigger than Tstatistic (2.902> 1.677); and (7) There was indirect influence of compensation on village head performance interfered by job satisfaction for 2.95% which Tvalue was bigger than Tstatistic (2.7047>1.677).  Keywords: Competency, Compensation, Job Statisfaction and village head performance village financial management